ENHANCING ENGLISH LISTENING SKILLS THROUGH STORY-BASED YOUTUBE CONTENT - NURILLO JAMBILOV XABIBILLOYEVICH, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Listening is one of the most fundamental yet challenging  skills in learning a foreign language. In English as a Foreign Language (EFL) contexts, learners often struggle  to  understand  authentic  spoken  input  due  to  limited  exposure,  lack  of motivation, and insufficient listening strategies. With the rapid development of digital technologies,  online  platforms  such  as  YouTube  have  become  powerful  tools  for language  learning.  This  article  explores  the  effectiveness  of  using  story-based YouTube content to enhance English listening skills among EFL learners. The study discusses theoretical foundations of listening comprehension, the pedagogical value of storytelling,  and practical  classroom  applications  of  YouTube stories. The  findings suggest  that  story-based  listening  materials  on  YouTube  significantly  improve learners’ listening comprehension, vocabulary acquisition, pronunciation awareness, and motivation. The article concludes that integrating YouTube stories into listening instruction is an effective and learner-centered approach in modern English language teaching.